Article 2330 of the Chilean Civil Code: A Review Regarding to Limits to the Strict Liability of the Defendant - Inostroza-Adasme, S (UNIV EXTERNADO COLOMBIA, 2022)
The article 2330 of the Chilean Civil Code stablishes at first glance that the compensation for damage due to the author s negligence can be lowered if the recklessness of the victim contributed to produce it. The question is whether such a reduction is applied to the author subject to strict responsibility, and if it is subject to limits in relation to its quantum or time. There would be no problem when that responsibility operates as negligence under the presumption of law, but it must be explained on principles of equity or procedural economy when its foundation is distributive justice, or when it is applied to victims by repercussion.